Experimental Evaluation of UWB-HB Transfer Function with LOS and NLOS for WBAN - Promwong, Sathaporn; Tiengthong, Thanadol; Chaisang, Aditep (My University, 2022)
Short-range wireless communication with low power and high data rate is a key to the future development of wireless body area network systems. Ultra-wideband technology can achieve the primary wireless communication requirements around the human vicinity. Hence, understanding the human body's effect on wireless communication systems is very important to investigate. This paper will present the evaluation scheme for the ultra-wideband human body channel characteristics in an indoor environment. The experimental is divided into two different scenarios, i.e., line-of-sight and non-line-of-sight, based on the actual wireless body area network applications. The experimental parameters cover the full band of the ultra-wideband regarding the FCC regulation of the ultra-wideband technology. The vector network analyzer and antennas are included in the experiment to measure and record the data. The channel transfer function evaluation results are path loss and delay characteristics. The contributions are useful for further development in the future wireless body area network applications as the basic knowledge of the human body effects.
Keywords: Friis' transmission formula; human body; impulse radio; UWB; WBAN